Serum IgE levels and severity of atopic dermatitis - Basnet, Binamra; Neupane, Saraswoti; Shrestha, Shristi (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Atopic dermatitis is an itchy, chronic relapsing, inflammatory skin condition with typical flexural distribution. The eruption is frequently associated with other atopic conditions in the individual or other family members . It is associated with increased production of serum IgE levels. The objective of this study is to evaluate whether serum IgE levels correlate with the severity of atopic dermatitis (AD) based on Three Item Severity (TIS) Score of AD. MATERIAL AND METHODS: This is a hospital based observational study carried out from June 2014 to January 2015. Eighty two atopic dermatitis patients aged ≤ 20 years were recruited from the OPD of Dermatology Department of Gandaki Medical College, and the AD severity was evaluated using TIS score (Three Item Severity score). Concentrations of serum total IgE were measured and compared with controls. RESULTS: The mean age of our study group comprising of 82 patients was 9.03±5.6 years. The overall TIS score was 5.74±2.02.To find out the correlation between the disease severity and IgE level, one way ANOVA test was used. There was no statistical difference between the IgE levels of controls and the patients with mild disease but there was a significant correlation between severity of disease (between mild, moderate and severe AD) and the levels of serum IgE. (P<0.05) CONCLUSION: Serum IgE is an useful indicator for predicting severity of atopic dermatitis in young patients.